2021
DOI: 10.3389/fcvm.2021.629547
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Pretreatment Mitigates Myocardial Ischemia/Reperfusion Injury via XBP1/GRP78/Akt Pathway

Abstract: Myocardial ischemia/reperfusion injury is a common clinical problem and can result in severe cardiac dysfunction. Previous studies have demonstrated the protection of electroacupuncture against myocardial ischemia/reperfusion injury. However, the role of X-box binding protein I (XBP1) signaling pathway in the protection of electroacupuncture was still elusive. Thus, we designed this study and demonstrated that electroacupuncture significantly improved cardiac function during myocardial ischemia/reperfusion inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The acupoint of Neiguan (PC6) is the most advised for the treatment of heart diseases in the theory of Chinese acupuncture. A wealth of evidence showed the bene ts of Neiguan (PC6) acupuncture for attenuating cardiac injury via multi-pathways, such as inhibiting apoptosis, alleviating mitochondrial damage, and decreasing the degree of in ammation [10,22,23]. In the present study, acupuncture at Neiguan (PC6) thickened the left ventricular wall in a rat model of MI and downregulated the expression of CC3.…”
Section: Discussionsupporting
confidence: 51%
“…The acupoint of Neiguan (PC6) is the most advised for the treatment of heart diseases in the theory of Chinese acupuncture. A wealth of evidence showed the bene ts of Neiguan (PC6) acupuncture for attenuating cardiac injury via multi-pathways, such as inhibiting apoptosis, alleviating mitochondrial damage, and decreasing the degree of in ammation [10,22,23]. In the present study, acupuncture at Neiguan (PC6) thickened the left ventricular wall in a rat model of MI and downregulated the expression of CC3.…”
Section: Discussionsupporting
confidence: 51%
“…ATF-6 transmembrane receptor proteins, which activates the PERK/eIF2α, IRE1α/XBP1, and ATF-6 pathway (Peralta & Brenner, 2011). I/R injury in the heart (N. Wang et al, 2021), brain (Gu et al, 2017), kidney (Y. Zhang et al, 2020), and liver (D. Liu, Jin, et al, 2018) significantly increases GRP78 expression.…”
Section: Discussionmentioning
confidence: 99%
“…ERS induces GRP78 dissociation from PERK, IRE1α, and ATF‐6 transmembrane receptor proteins, which activates the PERK/eIF2α, IRE1α/XBP1, and ATF‐6 pathway (Peralta & Brenner, 2011). I/R injury in the heart (N. Wang et al, 2021), brain (Gu et al, 2017), kidney (Y. Zhang et al, 2020), and liver (D. Liu, Jin, et al, 2018) significantly increases GRP78 expression. Jiao et al demonstrated that GRP78 expression is elevated in miniature pigs with hepatic I/R and partial resection injury.…”
Section: Discussionmentioning
confidence: 99%
“…XBP1 is one of the important proteins that mediate the occurrence of ERS, the effect of XBP1 on cells depends mainly on the strength of the injury and the degree of activation of XBP1. When the mice are pretreatment with small pre-stimulations such as low-frequency electrical stimulation, the low-level expression of XBP1 is induced then the body is provided with adaptive capacity, which is a protective measure, so that the less cell necrosisbody in body during subsequent severe damages such as hypoxia-reperfusion injury ( 61 ). However, if the cells suffer from strong oxidative stress, resulting in high expression of XBP1, it will lead to severe ERS and induce cell necrosis.…”
Section: Discussionmentioning
confidence: 99%